Crop Diversification Strategy to Improve Economic Value in Brazilian Sugarcane Production. (1st July 2018) - Borba de Moraes Farinelli, Juliana; Lopes Santos, David Ferreira; Fernandes, Carolina; Honorato Fernandes, Mariele Monique; Flavio da Silva, Matheus
Abstract : Core Ideas: The authors evaluated economically different treatments for sugarcane renewal. The authors present the impact of the diversification on sugarcane production on venture risk. The authors used the real options theory with a polynomial approach to model the managerial flexibility in exchanging sugarcane with soybean. Crop diversity is beneficial to rural properties in terms of reducing business risks and increasing agricultural revenues. In sugarcane ( Saccharum spp) farming, crop diversity using rotation or succession planting remains a paradigm for rural producers, largely because the productive cycle of sugarcane differs from that of annual crops, obliging farmers to grow it for between 4 and 6 yr to compensate for the high initial investment in planting. Sugarcane producers in Brazil only plant another crop at the end of the cycle to renew the plantation. The present study questions this paradigm by using the real options theory to capture the value of managerial flexibility in diversifying production to minimize risk and increase revenue by alternating between sugarcane and soybean ( Glycine max ) crops, considering a polynomial model that combines market and yield volatility. To that end, the research data were based on an experiment performed over 6 yr using different sugarcane succession systems on a rural property in the region of Jaboticabal, São Paulo, Brazil. Results suggest that succession planting of soybean/crotalaria/soybean/sugarcane exhibited the best agronomic and economic–financial performance and that diversifying crops using the portfolio theory increased the value of the project. Greater return on investment was obtained by replacing sugarcane with soybean, making it possible to opt for the crop change at the third cane cutting, a completely new scenario in Brazil, the largest sugarcane producer in the world.